Missing puzzle in crystal engineering: 2-pyridone and [1, 3, 5]-triazine-2, 4-diamine, the two most common cyclic hydrogen bonding sticky sites, in a single core. Issue 6 (23rd January 2023) - Abidi, Adela; Fortin, Emmanuelle; Larocque, Kariane; Essalhi, Mohamed; Dissem, Nour; Chartrand, Daniel; Maris, Thierry; Duong, Adam
Abstract : Herein, we report a facile method for the synthesis of eight structurally diverse compounds 1–8 bearing hydrogen bonding functional group – diaminotriazine (DAT) along with pyridine and polyether groups for 1–4 and DAT linked via C–C bond to a 2-pyridone for 5–8 . Abstract : Herein, we report a facile method for the synthesis of eight structurally diverse compounds 1–8 bearing hydrogen bonding functional group – diaminotriazine (DAT) along with pyridine and polyether groups for 1–4 and DAT linked via C–C bond to a 2-pyridone for 5–8 . These compounds are positional isomers and vary from each other in the position of DAT group with respect to the pyridine-nitrogen atoms. The successful synthesis of 1–8 was confirmed by infrared, mass spectrometry, and 1 H and 13 C nuclear magnetic resonance. Molecular structures and aggregations in the solid state of 1–5, and 7 were elucidated by single crystal X-ray diffraction (SCXRD) and showed predictable hydrogen bonding motifs for the DAT group. Among the four compounds with polyether chains, only 4 show an interdigitated pattern. The 2-pyridone group (in 5 and 7 ) shows none of the expected typical hydrogen bonding patterns. Rather, a heteroleptic hydrogen bonding motif involving the free hydrogen atom of the DAT group and the oxygen atom from the pyridones is observed. Overall, these hydrogen-bonded networks are mainly composed of layers (1 & 5 ), tapes (2 ), ribbons (3 & 7 ), and chains (4 ).